Association between serum vitamin D3 status and essential hypertension: a review - Patil, Divya V.; Dutta, Tarun Kumar (International Journal of Advances in Medicine, 2020)
The fat-soluble vitamin D is synthesized when the ultraviolet rays strike the surface of skin. The relationship between cardiovascular disease mainly arterial hypertension with low vitamin D levels is supported by literature. It has been observed that arterial hypertension has been associated with low levels of vitamin D. Obesity and reduced sunlight exposure are factors associated with lower serum vitamin D levels. Isolated systolic hypertension has been associated with vitamin D deficiency and insufficiency. Protective mechanism implicated in lowering the blood pressure is the suppression of renin angiotensin aldosterone pathway with optimal vitamin D levels. But randomised controlled trials are necessary to clarify whether vitamin D supplementation is beneficial in the control of blood pressure; as the results of many studies do not consistently favor the association of low vitamin D levels with hypertension.